Acute respiratory distress syndrome and acute lung injury. Issue 1031 (4th June 2011) - Dushianthan, A; Grocott, M P W; Postle, A D; Cusack, R
Abstract : Acute respiratory distress syndrome (ARDS) is a life threatening respiratory failure due to lung injury from a variety of precipitants. Pathologically ARDS is characterised by diffuse alveolar damage, alveolar capillary leakage, and protein rich pulmonary oedema leading to the clinical manifestation of poor lung compliance, severe hypoxaemia, and bilateral infiltrates on chest radiograph. Several aetiological factors associated with the development of ARDS are identified with sepsis, pneumonia, and trauma with multiple transfusions accounting for most cases. Despite the absence of a robust diagnostic definition, extensive epidemiological investigations suggest ARDS remains a significant health burden with substantial morbidity and mortality. Improvements in outcome following ARDS over the past decade are in part due to improved strategies of mechanical ventilation and advanced support of other failing organs. Optimal treatment involves judicious fluid management, protective lung ventilation with low tidal volumes and moderate positive end expiratory pressure, multi-organ support, and treatment where possible of the underlying cause. Moreover, advances in general supportive measures such as appropriate antimicrobial therapy, early enteral nutrition, prophylaxis against venous thromboembolism and gastrointestinal ulceration are likely contributory reasons for the improved outcomes. Although therapies such as corticosteroids, nitric oxide, prostacyclins, exogenous surfactants, ketoconazole and antioxidants have shown promising clinical effects in animal models, these have failed to translate positively in human studies. Most recently, clinical trials with β2 agonists aiding alveolar fluid clearance and immunonutrition with omega-3 fatty acids have also provided disappointing results. Despite these negative studies, mortality seems to be in decline due to advances in overall patient care. Future directions of research are likely to concentrate on identifying potential biomarkers or genetic markers to facilitate diagnosis, with phenotyping of patients to predict outcome and treatment response. Pharmacotherapies remain experimental and recent advances in the modulation of inflammation and novel cellular based therapies, such as mesenchymal stem cells, may reduce lung injury and facilitate repair.